2013
DOI: 10.1002/adma.201302927
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Quantum‐Confined Graphene‐Like States and Novel Hybrid States in Graphene Oxide by Transient Spectroscopy

Abstract: Quantum-confined graphene-like electronic states are directly observed in graphene oxide and photothermally reduced graphene oxide via transient spectroscopy. An unexpected novel hybrid state arising from amorphous carbon-like peripheral structure with high sp(3) /sp(2) carbon ratio in close vicinity of confined graphene-like states is found commonly existent in various carbon nanomaterials, including graphene oxide, graphene quantum dots, and carbon dots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 56 publications
7
58
0
Order By: Relevance
“…In addition, Yang et al reported that the green emission from oxygen-related function groups is strongly affected by reduction reaction. The charge separation could be observed in the green emission sample 20,21 . We also carry out the reduction experiment for all kinds of N-GQDs.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, Yang et al reported that the green emission from oxygen-related function groups is strongly affected by reduction reaction. The charge separation could be observed in the green emission sample 20,21 . We also carry out the reduction experiment for all kinds of N-GQDs.…”
Section: Resultsmentioning
confidence: 94%
“…Although the exact PL mechanism is still under debate, it has been demonstrated the PL of GQDs origining from electron-hole recombination, quantum size effect, zigzag sites, and defect effect 20,21,22 . Eda et al demonstrated that the blue emission was derived from isolated sp 2 cluster within carbon-oxygen sp 3 matrix, leading to radiative recombination of electron and hole 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, carbon dots (CDs) have been spotlighted to be a promising substitute to traditional metal-based semiconductor QDs because of their excellent properties, such as broadband optical absorption, good chemical stability, low toxicity, and attractive photoluminescence (PL) properties, [9][10][11] rendering them promising fluorophores for optoelectronic devices. [12][13][14][15][16] Chen's group has suggested CDs as a phosphor for WLEDs; however, these luminophores can hardly generate warm white light with high CRI for indoor lighting because of their low emission efficiency in the yellow and red regions.…”
mentioning
confidence: 99%
“…Ultrafast spectroscopy is a powerful tool for investigating the electronic structure, excitonic properties and carrier dynamics for various new types of fluorescent nanomaterials, for example, graphene oxide, 35,36 graphene quantum dots (QDs), 37 carbon nanodots, 38,39 polymer nanoparticles, 40 direct bandgap semiconductor QDs 41243 and Si NCs. 44249 In our previous work, we produced novel Si NCs with unprecedented ultrabright fluorescence and single-exponential decay.…”
Section: Introductionmentioning
confidence: 99%